EFISIENSI DAN AKUNTABILITAS DALAM PENGELOLAAN DANA PENDIDIKAN: PERSEPEKTIF MANAJEMEN STRATEGIK - Shofiyyah, Alya; Yusup, Ilham; Weki Sera, Salvator Ronaldo; Widyatmike, G. M. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The management of education funds in Indonesia is an important aspect in improving the quality of education that is equitable and quality. This paper discusses the efficiency and accountability in the management of education funds by emphasizing the application of strategic management in education policies. Through a qualitative approach, an analysis is conducted on the education fund policies implemented by the government, such as the School Operational Assistance Fund (BOS) and the Smart Indonesia Program (PIP), and how these two policies contribute to the equality and improvement of education quality. This paper also explains the challenges faced in fund management, such as the uneven distribution of funds and the lack of transparency in some regions. Recommendations for improving the efficiency and accountability of education fund management include a better monitoring system, fund manager training, and higher transparency in the use of education funds. It is hoped that with the implementation of these recommendations, the management of education funds in Indonesia can be more optimal and have a positive impact on improving the quality of education as a whole.